Mechanics of materials SI version - Philpot, Timothy A. ([Place of publication not identifed] : John Wiley & Son, Inc., 2014)
This book presents the theory and practice of mechanics of materials in a straight-forward, plain-speaking, student-friendly manner that addresses the learning styles of today's students without sacrificing rigor or depth in the presentation of topics.
Chapter 1. Stress -- 11.1 Introduction -- 11.2 Normal Stress Under Axial Loading -- 11.3 Direct Shear Stress -- 11.4 Bearing Stress -- 11.5 Stresses on Inclined Sections -- 11.6 Equality of Shear Stresses on Perpendicular Planes -- Chapter 2. Strain -- 2.1 Displacement, Deformation, and the Concept of Strain -- 2.2 Normal Strain -- 22.3 Shear Strain -- 2.4 Thermal Strain -- Chapter 3. Mechanical Properties of Materials -- 3.1 The Tension Test -- 3.2 The Stress Strain Diagram -- 3.3 Hooke's Law -- 3.4 Poisson's Ratio -- Chapter 4. Design Concepts -- 4.1 Introduction -- 4.2 Types of Loads -- 4.3 Safety -- 4.4 Allowable Stress Design -- 4.5 Load and Resistance Factor Design -- Chapter 5. Axial Deformation -- 5.1 Introduction -- 5.2 Saint-Venant's Principle -- 5.3 Deformations in Axially Loaded Bars -- 5.4 Deformations in a System of Axially Loaded Bars -- 5.5 Statically Indeterminate Axially Loaded Members -- 5.6 Thermal Effects on Axial Deformation -- 5.7 Stress Concentrations -- Chapter 6. Torsion -- 6.1 Introduction -- 6.2 Torsional Shear Strain -- 6.3 Torsional Shear Stress -- 6.4 Stresses on Oblique Planes -- 6.5 Torsional Deformations -- 6.6 Torsion Sign Conventions -- 6.7 Gears in Torsion Assemblies -- 6.8 Power Transmission -- 6.9 Statically Indeterminate Torsion Members -- 6.10 Stress Concentrations in Circular Shafts Under Torsional Loadings -- 6.11 Torsion of Noncircular Sections -- 6.12 Torsion of Thin-Walled Tubes: Shear Flow -- Chapter 7. Equilibrium of Beams -- 7.1 Introduction -- 7.2 Shear and Moment in Beams -- 7.3 Graphical Method for Constructing Shear and Moment Diagrams -- 7.4 Discontinuity Functions to Represent Load, Shear, and Moment -- Chapter 8. Bending -- 8.1 Introduction -- 8.2 Flexural Strains -- 8.3 Normal Stresses in Beams -- 8.4 Analysis of Bending Stresses in Beams -- 8.5 Introductory Beam Design for Strength -- 8.6 Flexural Stresses in Beams of Two Materials -- 8.7 Bending Due to Eccentric Axial Load -- 8.8 Unsymmetric Bending -- 8.9 Stress Concentrations Under Flexural Loadings -- Chapter 9. Shear Stress in Beams -- 9.1 Introduction -- 9.2 Resultant Forces Produced by Bending Stresses -- 9.3 The Shear Stress Formula -- 9.4 The First Moment of Area Q -- 9.5 Shear Stresses in Beams of Rectangular Cross Section -- 9.6 Shear Stresses in Beams of Circular Cross Section -- 9.7 Shear Stresses in Webs of Flanged Beams -- 9.8 Shear Flow in Built-Up Members -- 9.9 Shear Stress and Shear Flow in Thin-Walled Members -- 9.10 Shear Centers of Thin-Walled Open Sections -- Chapter 10. Beam Deflections -- 10.1 Introduction -- 10.2 Moment-Curvature Relationship -- 10.3 The Differential Equation of the Elastic Curve -- 10.4 Deflections by Integration of a Moment Equation -- 10.5 Deflections by Integration of Shear-Force or Load Equations -- 10.6 Deflections Using Discontinuity Functions -- 10.7 Method of Superposition -- Chapter 11. Statically Indeterminate Beams -- 11.1 Introduction -- 11.2 Types of Statically Indeterminate Beams -- 11.3 The Integration Method -- 11.4 Use of Discontinuity Functions for Statically Indeterminate Beams -- 11.5 The Superposition Method -- Chapter 12. Stress Transformations -- 12.1 Introduction -- 12.2 Stress at a General Point in an Arbitrarily Loaded Body -- 12.3 Equilibrium of the Stress Element -- 12.4 Plane Stress -- 12.5 Generating the Stress Element -- 12.6 Equilibrium Method for Plane Stress Transformations -- 12.7 General Equations of Plane Stress Transformation -- 12.8 Principal Stresses and Maximum Shear Stress -- 12.9 Presentation of Stress Transformation Results -- 12.10 Mohr's Circle for Plane Stress -- 12.11 General State of Stress at a Point -- Chapter 13. Strain Transformations -- 13.1 Introduction -- 13.2 Plane Strain -- 13.3 Transformation Equations for Plane Strain -- 13.4 Principal Strains and Maximum Shearing Strain -- 13.5 Presentation of Strain Transformation Results -- 13.6 Mohr's Circle for Plane Strain 58113.7 Strain Measurement and Strain Rosettes 58513.8 Generalized Hooke's Law for Isotropic Materials -- Chapter 14. Thin-Walled Pressure Vessels -- 14.1 Introduction -- 14.2 Spherical Pressure Vessels -- 14.3 Cylindrical Pressure Vessels -- 14.4 Strains in Pressure Vessels -- Chapter 15. Combined Loads -- 15.1 Introduction -- 15.2 Combined Axial and Torsional Loads -- 15.3 Principal Stresses in a Flexural Member -- 15.4 General Combined Loadings -- 15.5 Theories of Failure -- Chapter 16. Columns -- 16.1 Introduction -- 16.2 Buckling of Pin-Ended Columns -- 16.3 The Effect of End Conditions on Column Buckling -- 16.4 The Secant Formula -- 16.5 Empirical Column Formulas' Centric Loading -- 16.6 Eccentrically Loaded Columns -- Chapter 17. Energy Methods -- 17.1 Introduction -- 17.2 Work and Strain Energy -- 17.3 Elastic Strain Energy for Axial Deformation -- 17.4 Elastic Strain Energy for Torsional Deformation -- 17.5 Elastic Strain Energy for Flexural Deformation -- 17.6 Impact Loading -- 17.7 Work-Energy Method for Single Loads -- 17.8 Method of Virtual Work -- 17.9 Deflections of Trusses by the Virtual-Work Method -- 17.10 Deflections of Beams by the Virtual-Work Method -- 17.11 Castigliano's Second Theorem -- 17.12 Calculating Deflections of Trusses by Castigliano's Theorem -- 17.13 Calculating Deflections of Beams by Castigliano's Theorem -- Appendix A. Geometric Properties of an Area -- A.1 Centroid of an Area -- A.2 Moment of Inertia for an Area -- A.3 Product of Inertia for an Area -- A.4 Principal Moments of Inertia -- A.5 Mohr's Circle for Principal Moments of Inertia -- Appendix B. Geometric Properties of Structural Steel Shapes -- Appendix C. Table of Beam Slopes and Deflections -- Appendix D. Average Properties of Selected Materials -- Answers to Odd Numbered Problems -- Index 871.
Includes index.
Keywords: STRENGTH THEORY